2016
DOI: 10.1177/1098612x15622806
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam in the management of feline audiogenic reflex seizures: a randomised, controlled, open-label study

Abstract: Objectives Currently, there are no published randomised, controlled veterinary trials evaluating the efficacy of antiepileptic medication in the treatment of myoclonic seizures. Myoclonic seizures are a hallmark of feline audiogenic seizures (FARS). Methods This prospective, randomised, open-label trial compared the efficacy and tolerability of levetiracetam (20-25 mg/kg q8h) with phenobarbital (3-5 mg/kg q12h) in cats with suspected FARS that experienced myoclonic seizures. Cats were included that had ⩾12 myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
(46 reference statements)
3
30
0
Order By: Relevance
“…37,41 Recent evidence in cats indicated that levetiracetam decreased myoclonic seizure frequency by >50% whereas phenobarbital had a negligible effect in the management of myoclonic seizures in cats with FARS. 46 This study strongly supports the use of levetiracetam in myoclonic seizures although currently management of epileptic myoclonus (eg, Lafora disease) in dogs with levetiracetam is based predominantly on anecdotal experience.…”
Section: Treatmentsupporting
confidence: 65%
“…37,41 Recent evidence in cats indicated that levetiracetam decreased myoclonic seizure frequency by >50% whereas phenobarbital had a negligible effect in the management of myoclonic seizures in cats with FARS. 46 This study strongly supports the use of levetiracetam in myoclonic seizures although currently management of epileptic myoclonus (eg, Lafora disease) in dogs with levetiracetam is based predominantly on anecdotal experience.…”
Section: Treatmentsupporting
confidence: 65%
“…The C max was higher than the maximal reference interval for humans (45 μg/mL) in all cats, but adverse effects were minimal and neurologic examination findings remained normal in all cats, indicating tolerance of the increased C max . Reported adverse effects in cats after PO levetiracetam administration include lethargy, anorexia, ataxia, polydipsia, and hypersalivation . After multi‐dose administration of IRL, a reported 18% of cats developed adverse effects, but all signs resolved within a 2‐week period without dose adjustment .…”
Section: Discussionmentioning
confidence: 99%
“…Levetiracetam is an AED approved for use in humans. Its novel mechanism of action coupled with minimal reported adverse effects makes it an appealing drug for seizure control in cats . Pharmacokinetics of intermediate‐release levetiracetam (IRL)‐administered PO in cats support a 20–25 mg/kg dosage, but the short elimination half‐life of 2.95 ± 0.95 hours necessitates a q8h dosing regimen, decreasing owner compliance .…”
mentioning
confidence: 99%
“…Epileptic seizures are the most common reason cats are presented to veterinary neurologists and often antiepileptic drugs (AED) are recommended for long‐term seizure control regardless of the etiologic diagnosis. Although many cats have favorable seizure control with PO administration of phenobarbital and intermediate‐release levetiracetam (IRL), administration 2–3 times daily long‐term may be difficult for owners, leading to poor compliance.…”
Section: Introductionmentioning
confidence: 99%